2017
DOI: 10.1111/pai.12702
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ovomucoid‐specific low‐affinity IgE in infants and its relationship to eczema

Abstract: Human infant peripheral blood contains allergen-specific low-affinity sIgE. Persistent eczema is related to the development of high-affinity, but not low-affinity, IgE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Furthermore, a strong association between food sensitization and atopic dermatitis and/or skin barrier impairment has been reported . We reported previously the presence of strong association between persistent eczema and high incidence of ovomucoid‐specific high‐affinity IgE in 14‐month‐old infants . The present longitudinal study of immunoglobulin isotype formation found low levels of IgG1, undetectable levels of IgG2 and high levels and high‐affinity IgE in the red circles infants, suggests that this type of immunoglobulin isotype formation is closely related to eczema history and could potentially be a biomarker of progression of food allergy.…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Furthermore, a strong association between food sensitization and atopic dermatitis and/or skin barrier impairment has been reported . We reported previously the presence of strong association between persistent eczema and high incidence of ovomucoid‐specific high‐affinity IgE in 14‐month‐old infants . The present longitudinal study of immunoglobulin isotype formation found low levels of IgG1, undetectable levels of IgG2 and high levels and high‐affinity IgE in the red circles infants, suggests that this type of immunoglobulin isotype formation is closely related to eczema history and could potentially be a biomarker of progression of food allergy.…”
Section: Discussionsupporting
confidence: 63%
“…For instance, correlation coefficient of casein‐specific IgE between UniCAP (kU A /L) and DCP microarray (BUe/mL) and its equation are shown in Figure S1. Based on the small volume of the blood sample and wide assay dynamic range, the DCP assay method has been used in several cohort studies …”
Section: Methodsmentioning
confidence: 99%
“…In Japan, persistent eczema is related to the development of high-affinity, but not low-affinity, IgE against ovomucoid. 31 Fruit and vegetable intake is not associated with asthma or chronic rhino-sinusitis in European adults. 32…”
Section: Food Allerg En Smentioning
confidence: 97%
“…In Japan, persistent eczema is related to the development of high‐affinity, but not low‐affinity, IgE against ovomucoid …”
Section: Food Allergensmentioning
confidence: 99%